Testing, simulation and design of press-braked ferritic stainless steel slender channel section columns failing by local–flexural interactive buckling - Li, Shuai (2023)
This paper presents an experimental and numerical study of the local–flexural interactive buckling behaviour and resistances of press-braked ferritic stainless steel slender channel section columns. An experimental programme was firstly conducted, including initial geometric imperfection measurements and ten pin-ended column tests. Interaction between local buckling and flexural buckling was observed for all column specimens upon testing and discussed in detail. The test results were used in a parallel numerical modelling programme to validate finite element models, which were then adopted to perform parametric studies to generate additional numerical data over a wide range of cross-section dimensions and member effective lengths. Based on the test and numerical data, the relevant design rules for press-braked ferritic stainless steel slender channel section columns, as given in the American specification and European code, were evaluated. The evaluation results revealed that the American specification resulted in a good level of design accuracy, while the European code led to conservative and scattered interactive buckling resistance predictions. Finally, a revised Eurocode design method was proposed and shown to yield much more accurate and consistent interactive buckling resistance predictions for press-braked ferritic stainless steel slender channel section columns than its original counterpart.